ANGIOGENIC IMBALANCES IN THE PATHOGENESIS OF PREGNANCY COMPLICATIONS. (17th September 2014) - ESPINOZA, JIMMY
<x content-type="archive" xml:space="preserve">Abstract</x> Endothelial cell proliferation and survival require continuous low levels of vascular endothelial growth factor (VEGF). The bioavailability of this angiogenic factor appears to be regulated by anti-angiogenic factors, including the soluble form of VEGF receptor 1 (sFlt-1) in the non-pregnant and pregnant states. During pregnancy a VEGF antagonist (sFlt-1) and other anti-angiogenic factors, including soluble endoglin (s-Eng), are produced by the human placenta and released into the maternal circulation; an excess of these anti-angiogenic factors can lead into angiogenic imbalances and pregnancy complications. This is important because regulation of VEGF action on angiogenic balances appears to be essential for a successful pregnancy.